2020
DOI: 10.1017/s0033583520000013
|View full text |Cite
|
Sign up to set email alerts
|

Anionic food color tartrazine enhances antibacterial efficacy of histatin-derived peptide DHVAR4 by fine-tuning its membrane activity

Abstract: Here it is demonstrated how some anionic food additives commonly used in our diet, such as tartrazine (TZ), bind to DHVAR4, an antimicrobial peptide (AMP) derived from oral host defense peptides, resulting in significantly fostered toxic activity against both Gram-positive and Gram-negative bacteria, but not against mammalian cells. Biophysical studies on the DHVAR4–TZ interaction indicate that initially large, positively charged aggregates are formed, but in the presence of lipid bilayers, they rather associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…The short FK-16 showed an intermediate behaviour forming particles with both features. Similar morphology has already been observed for peptide associates formed with various binding partners such as LL-37 with RNA 47 , CM15 with the therapeutic drug suramin 21 , or Dhvar4 with the food colour tartrazine 23 . All these findings suggest that formation of such semi-folded assemblies might be common in interactions of amphipathic peptides with natural or synthetic small molecules.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The short FK-16 showed an intermediate behaviour forming particles with both features. Similar morphology has already been observed for peptide associates formed with various binding partners such as LL-37 with RNA 47 , CM15 with the therapeutic drug suramin 21 , or Dhvar4 with the food colour tartrazine 23 . All these findings suggest that formation of such semi-folded assemblies might be common in interactions of amphipathic peptides with natural or synthetic small molecules.…”
Section: Resultssupporting
confidence: 76%
“…AMPs along the gastro-intestinal tract were also considered, such as buforin I, a human gastric fluid AMP 39 , and Dhvar4, a potent AMP variant developed from human saliva histatins 40 . For the latter, interaction with food color small molecules affecting its membrane activity has been reported 23 . As reference, peptides already investigated for hemin interaction in the absence of lipid bilayers 19 such as the bee venom component melittin and its hybrid CM15 were also studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pure lipid system was characterized by isolated, spherical-shaped,~100 nm-sized, unilamellar vesicles (Figure 4B), while the interaction with LL-37 promoted the contacts between the lipid vesicles, leading to a "shell-packed" morphology (Figure 4C) with a group of nearby vesicles enclosed in a shell-like envelope. Previous investigations on the cationic peptide DHVAR4 with anionic membranes showed similar behaviour, where small groups of closely located vesicles were embedded into larger shell-like structures [89].…”
Section: Effect Of the Peptides On The Size And Morphology Of Model Vesiclesmentioning
confidence: 65%
“…Their actions also involve a variety of inflammatory and immunomodulatory responses ( Alba, Lopez-Abarrategui and Otero-Gonzalez 2012 ; Hancock et al, 2016 ). Moreover, besides their monomeric form, an increasing amount of data indicate that their supramolecular self- or co-assembled scaffolds can also have functional relevance ( Lee et al, 2019 ; Engelberg and Landau 2020 ; Ricci et al, 2020 ; Quemé-Peña et al, 2021 ). It has also been shown that various small organic molecules as well as lipid clusters trigger the disorder-to-order conformational transition of intrinsically unfolded AMPs, facilitating their oligomerization and complex formation, which can also affect the peptide function in vivo ( Ricci et al, 2020 ; Quemé-Peña et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%